Pocket Atlas of Sectional Anatomy, Volume II Computed Tomography and Magnetic Resonance Imaging. - Moeller, Torsten Bert (Thieme Medical Publishers, Incorporated, 2013)
"This comprehensive, easy-to-consult pocket atlas is renowned for its superb illustrations and ability to depict sectional anatomy in every plane. Together with its two companion volumes, it provides a highly specialized navigational tool for all clinicians who need to master radiologic anatomy and accurately interpret CT and MR images. Special features of Pocket Atlas of Sectional Anatomy: - Didactic organization in two-page units, with high-quality radiologic images on one side and brilliant, full-color diagrams on the other - Hundreds of high-resolution CT and MR images, many made with the latest generation of scanners (e.g., 3T MRI, 64-slice CT) - Consistent color coding, making it easy to identify similar structures across several slices - Concise, easy-to-read labeling of all figures. Updates for the 4th edition of Volume I: - New cranial CT imaging sequences of the axial and coronal temporal bone - Expanded MR section, with all new 3T MR images of the temporal lobe and hippocampus, basilar artery, cranial nerves, cavernous sinus, and more - New arterial MR angiography sequences of the neck and additional larynx images Compact, easy-to-use, highly visual, and designed for quick recall, this book is ideal for use in both the clinical and study settings. Volume I: Head and Neck Volume II: Thorax, Heart, Abdomen, and Pelvis, ISBN 978-3-13-125604-1 Volume III: Spine, Extremities, Joints, ISBN 978-3-13-143171-4 Torsten B. Moeller, MD, and Emil Reif, MD, Department of Radiology, Marienhaus Klinikum Saarlouis-Dillingen, Dillingen/Saarlouis, Germany"--Provided by publisher.